2019
DOI: 10.1111/febs.14772
|View full text |Cite
|
Sign up to set email alerts
|

MAVS polymers smaller than 80 nm induce mitochondrial membrane remodeling and interferon signaling

Abstract: Double‐stranded RNA (ds RNA ) is a potent proinflammatory signature of viral infection and is sensed primarily by RIG ‐I‐like receptors ( RLR s). Oligomerization of RLR s following binding to cytosolic ds RNA activates and nucleates self‐assembly of the mitochondrial antiviral‐signaling protein ( MAVS ). In the current signaling model, the caspase recr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity Buskiewicz et al reported that chemically generated oxidative stress (using glucose oxidase) stimulated the formation of MAVS oligomers, which led to mitochondrial hyperpolarization and decreased ATP production and spare respiratory capacity [29]. MAVS oligomerization directly suppresses the function of mitochondrial complexes I to IV and trigger the deficiency of ATP and the effusion of Cyto C [30]. Based on their findings, we speculate that MAVS involves in radiosensitivity through its oligomerization mediated by ROS.…”
Section: Discussionsupporting
confidence: 51%
“…Oxidative Medicine and Cellular Longevity Buskiewicz et al reported that chemically generated oxidative stress (using glucose oxidase) stimulated the formation of MAVS oligomers, which led to mitochondrial hyperpolarization and decreased ATP production and spare respiratory capacity [29]. MAVS oligomerization directly suppresses the function of mitochondrial complexes I to IV and trigger the deficiency of ATP and the effusion of Cyto C [30]. Based on their findings, we speculate that MAVS involves in radiosensitivity through its oligomerization mediated by ROS.…”
Section: Discussionsupporting
confidence: 51%
“…It is well established that MAVS is C-terminally anchored on the OMM and that the formation of large MAVS aggregates causes substantial changes to mitochondrial morphology ( Cai et al, 2014 ; Hou et al, 2011 ; Xu et al, 2015 ). Even endogenous levels of MAVS aggregates are sufficient to drive apoptosis, which is dependent on the MAVS transmembrane domain, likely linked to MAVS-driven mitochondrial fragmentation ( Hwang et al, 2019 ). Driving such morphological changes are MAVS-dependent mitochondrial ROS generation, mitochondrial membrane hyperpolarization, inhibition of spare respiratory capacity, and modulation of ATP synthesis (see below; Buskiewicz et al, 2016 ; Lei et al, 2009 ).…”
Section: Mitochondrial Innate Immune Signalingmentioning
confidence: 99%
“…1a, b, "poly(I:C)-LMW"), suggesting that Mff plays a critical role in the MAVS-mediated antiviral response. Mitochondrial morphological changes after the viral RNA introduction 27,29,43,44 were severely repressed in Mff KO MEFs and in Drp1 KO MEFs ( Supplementary Fig. 1e).…”
Section: Resultsmentioning
confidence: 97%